Effect of particle size on dielectric properties and hysteresis behavior of 0-3 barium zirconate titanate-portland cement composites - Ruamporn Potong (2018)
In this work, the effect of barium zirconate titanate (BZT) particle size on the dielectric properties and hysteresis behavior of 0-3 Barium zirconate titanate- Portland cement composites was investigated. BZT of various particle sizes (75, 212 and 425 μm) were used at 50% by volume to produce the 0-3 lead-free composites. The results showed that the dielectric constant at 1 kHz of composite was ≈ 350, while dielectric loss decreased with increasing particle size of BZT ceramics. It is clear from the hysteresis measurements that the particle size has a strong influence on the polarization-electric field loop of composites. The composite at 425 μm particle size was found to exhibit a more typical ferroelectric hysteresis loop. © 2013 Copyright Taylor and Francis Group, LLC.